Leonesiella tetratriches sp. nov. from the Cantabrian Mountains (León, Spain)—first species of Cantabrian Leptodirini found in mesovoid shallow substratum (MSS) (Coleoptera, Leiodidae, Cholevinae, Leptodirini) - Fresneda, Javier; Ortuño, Vicente M.; Arribas, Óscar; Salgado, José María (Zootaxa, 2026)
A new Leptodirini, Leonesiella tetratriches sp. nov. (Coleoptera, Leiodidae, Cholevinae), is described from siliceous mesovoid shallow substratum (MSS) at two localities in the Cantabrian Mountains (Salientes Valley, León, Spain). This species is closely related to Leonesiella bergidi (Salgado, 1983) with which it shares the shape of body, antennae, legs, spermathecal complex, aedeagus, metatergal apparatus and metendosternite. It differs in the structure of the mesoventral keel, in the suture of the metaventrite, in structures of the endophallus, and especially in the shape of the stylet and the presence of four setae at the apex of the parameres. The sampling technique, distribution of the two species, and differentiating morphological characters are illustrated.